Manganese complexes of curcumin analogues: Evaluation of hydroxyl radical scavenging ability, superoxide dismutase activity and stability towards hydrolysis - Opa Vajragupta (2018)
In order to improve the antioxidant property of curcumin and its analogue, diacetylcurcumin, manganese was incorporated into the structures in order to enhance superoxide dismutase (SOD) activity. Manganese (Mn) complexes of curcumin (CpCpx) and diacetylcurcumin (AcylCpCpx) were synthesized and firstly investigated for SOD activity and hydroxyl radical (HO•) scavenging ability. SOD activity was evaluated by both the nitroblue tetrazolium (NBT) reduction assay and electron paramagnetic resonance (EPR) with 5,5-dimethyl-1-pyrroline-N-oxide (DMPO) as a spin trapping agent. CpCpx and AcylCpCpx inhibited the NBT reduction and decreased the DMPO/OOH adduct much greater than corresponding antioxidants or ligands, with IC50values of 29.9 and 24.7 μM (NBT), and 1.09 and 2.4O mM (EPR), respectively. For EPR, potassium superoxide (KO2) was used as a source of O2-•where qualitative results suggested that CpCpx and AcylCpCpx were SOD mimics, which catalyze the conversion of O2-•to dioxygen and hydrogen peroxide (H2O2). Additionally, CpCpx and AcylCpCpx exhibited the great inhibition of DMPO/OH adduct formation with an IC50of 0.57 and 0.37 mM, respectively, which were comparable to that of curcumin (IC50of 0.64 mM), indicating that both Mn complexes are also an effective HO• scavenger. The stability against hydrolysis in water, various buffers and human blood/serum was carried out in vitro. It was found that both Mn complexes were pH and salt concentration dependent, being more stable in basic pH. In the human blood/serum test, CpCpx was more stable against hydrolysis than AcylCpCpx with about 10 and 20% of free Mn2+-releasing, respectively. © 2004 Taylor & Francis Ltd.